Information Security Applications 9th International Workshop, WISA 2008, Jeju Island, Korea, September 23-25, 2008, Revised Selected Papers - Sohn, Kiwook; Yung, Moti (Security and Cryptology, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International Workshop on Information Security Applications, WISA 2008, held in Jeju Island, Korea, during September 23-25, 2008. The 24 revised full papers presented were carefully reviewed and selected from a total of 161 submissions. The papers are organized in topical sections on smart card and secure hardware, wireless and sensor network security, public key crypto applications, privacy and anonymity, n/w security and intrusion detection, as well as application security and trust management.